Collective Total Synthesis of β-Carboline-Type Monoterpenoid Indole Alkaloid Glycosides - Sakamoto, Jukiya; Hiruma, Daiki; Kitajima, Mariko; Ishikawa, Hayato (Synlett, 2023)
The collective and efficient asymmetric total syntheses of five β-carboline-type monoterpenoid indole alkaloid glycosides were achieved in fewer than thirteen steps. A Pictet–Spengler reaction with α-cyanotryptamine followed by the removal of the cyano group and autoxidation (aromatization) efficiently constructed the β-carboline motif. In addition, bioinspired reactions were developed to provide different alkaloid skeletons.
Keywords: bioinspired reaction; monoterpenoid indole alkaloid; β-carboline; decyanation; Pictet–Spengler reaction